The Effectiveness of Experiential Learning to Promote Speaking Skills of the Eleventh Grade Students in SMAN 2 Palangka Raya - Muhammad Rezeki (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is aimed to measure the effect of experiential learning method to the speaking skills of the eleventh grade students of SMAN 2 Palangka Raya. In this study, the researcher used quasi-experimental design, where the researcher used nonrandomized control group pre-test, post-test design with a kind of treatment. In this study the researcher was helped by the English teacher of SMAN 2 Palangka Raya as the second tester for pre-test and post-test. In this experiment, the researcher taught the students directly with the same material. Therefore, the use of experiential learning method was applied on experiment group only, and for the control group the researcher applied conventional method. Meanwhile, the control group was not given the treatment. To examine the hypothesis, the researcher used t-test formula. In addition, the researcher used SPSS V 25 program to compare the data. The result of t test using manual calculation showed that the calculated value of tobserved was greater than the value of ttable at 5% significance level or 2.000 < 2.0312 < 2.660 and lower at 1%. the value of Tobserved was greater than the value of Ttable at 5% but lower at 1% significance level or 2.000 < 2.0312 < 2.660. The result of t-test using SPSS V 25 calculation found the calculated value (tobserved) Tobserved was greater than Ttable at 5% but lower at 1% significance level or 2.000 < 2.059 < 2.660. This indicated that the alternative hypothesis stating that there is significant effect of using experiential learning method toward students’ speaking score at eleventh grade students in SMAN 2 Palangka Raya was accepted and Ho stating that there is no significant effect of using experiential learning method toward students’ speaking score at eleventh grade students in SMAN 2 Palangka Raya was rejected. It meant that Experiential learning give significant effect to the students’ score. The result of t test using manual calculation showed that the calculated value of tobserved was greater than the value of ttable at 5% significance level or 2.000 < 2.0312 < 2.660 and lower at 1%. the value of Tobserved was greater than the value of Ttable at 5% but lower at 1% significance level or 2.000 < 2.0312 < 2.660. The result of t-test using SPSS V 25 calculation found the calculated value (tobserved) Tobserved was greater than Ttable at 5% but lower at 1% significance level or 2.000 < 2.059 < 2.660. This indicated that the alternative hypothesis stating that there is significant effect of using experiential learning method toward students’ speaking score at eleventh grade students in SMAN 2 Palangka Raya was accepted and Ho stating that there is no significant effect of using experiential learning method toward students’ speaking score at eleventh grade students in SMAN 2 Palangka Raya was rejected. It meant that Experiential learning give significant effect to the students’ score